IMPROVING STUDENT LEARNING OUTCOMES WITH THE INQUIRY LEARNING MODEL USED BY GOOGLE FORM MEDIA ON IMPULSE AND MOMENTUM MATERIAL IN GRADE X OF SMA ASUHAN DAYA MEDAN IN THE 2023/2024 ACADEMIC YEAR. - Jesica (Jurnal Edukasi dan Pembelajaran STEM, 2025)
The purpose of this research is to determine the improvement in performance and learning outcomes of Physics with the Google Form Assisted Inquiry Learning Model for Class X SMA Asuhan Daya Medan. The type of research used is classroom action research which aims to determine whether there is an increase in performance and learning outcomes of the subjects, namely students. The population of this research is all students of Class X SMA Asuhan Daya Medan. The sample is class X-IPA, totaling 25 students, who are taught using the inquiry learning model based on the concept of freedom of learning. This type of research is carried out using two cycles to achieve good learning outcomes. The instrument in this question consists of 14 multiple-choice questions with options (a, b, c, d and e) which are tested for validity, reliability and level of test difficulty. Learning outcomes are obtained using the Gain value according to the results of the hypothesis test, learning outcomes increase from ???? ̅ pre-cycle = 36.36 to ???? ̅ cycle I = 68.91 N-Gain = 0.44 and is classified as neutral. learning improvement from ???? ̅ diaphragm = 36.36 ???? ̅ cycle II = 85.09 with N-Gain = 0.74 is classified as high. The increase in learning activity ???? ̅ cycle I meeting 1 = 40.94 to ???? ̅ cycle and I fulfill the first N-Gain = 0.19 less classified as meeting 2 = 52.00, then the learning activity increases ???? ̅ cycle I 1 = 40.94 to meeting II = 66.06 seconds N With - Gain = 0.42 is classified as moderate, and the increase in active learning ???? ̅ cycle I meeting 1 = 40.91 to ???? ̅ cycle II meeting 2 = 85.09 with the third N-Gain = 0.85 is classified as high. The results of this research show an increase in performance and higher learning outcomes in the learning process using the Google Form Assisted Inquiry Learning Model for Class X of SMA Asuhan Daya Medan in the 2023/2024 academic year.